Eksistensi Tradisi Igel Desa dal Eksistensi Tradisi Igel Desa dalam Upacara Piodalan di Pura Desa, Desa Adat Nagasepaha: Eksistensi Tradisi Igel Desa dalam Upacara Piodalan di Pura Desa, Desa Adat Nagasepaha - Kadek Koriani; Ni Nyoman Suastini; Putu Agus Panca Saputra (Jurnal Widya Sastra Pendidikan Agama Hindu, 2026)
This research aims to explore the existence of the Igel Desa tradition within the Piodalan ceremony held at Pura Desa, Nagasepaha Traditional Village, Buleleng District, Buleleng Regency. Three core issues are investigated: (1) the procedural stages of the Igel Desa tradition, (2) the role of this tradition in community life, and (3) the Hindu Religious Education values embedded within it. The study adopts a descriptive qualitative approach, gathering data through field observation, in-depth interviews, and document review. Participants were determined through purposive and snowball sampling strategies. The theoretical underpinnings draw from the Theory of Religion (Koentjaraningrat), Ritual Theory (Victor Turner), Structural Functionalism (Durkheim and Parsons), and Value Theory (Kluckhohn and Spranger). Findings reveal that the Igel Desa tradition unfolds across three ceremonial phases: pre-liminal (the gathering and preparation of Krama desa at the jaba tengah pura), liminal (communal prayers and sacred dance performance accompanied by the telung kempul gamelan), and post-liminal (ritual self-purification through touching a candle). The tradition carries religious, social, cultural, educational, and aesthetic dimensions. Hindu Religious Education values embedded within include Tattwa, Susila, and Upacara. The Igel Desa tradition has been shown to serve as an effective non-formal educational platform for transmitting Hindu values to the younger generation. Keywords: Balinese Tradition, Igel Desa, Hindu Religious Education, Nagasepaha Traditional Village Piodalan.